(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
Cervical cancer shows a high prevalence among Bangladeshi women. Reports indicated that oxidant-antioxidant balance plays a role in cervical cancer pathogenesis. Therefore, this study explores the change of different blood-derived enzymes, antioxidants, and biomarkers to understand the oxidative stress status of Bangladeshi cervical cancer patients. A clinician recruited the case and control participants for the study based on histopathologic reports. No significant difference was observed in the random blood glucose level, blood pressure, total cholesterol, triglycerides (TGs), HDL cholesterol, LDL cholesterol, and total protein levels in case participants compared to age and sex-matched control subjects. However, serum albumin, vitamins like alpha-tocopherol and ascorbic acid, antioxidant enzymes like SOD, and catalase levels significantly decreased in patients compared to controls. Other parameters, like, ALT, AST, ALP, phospholipid hydroperoxide, TBARS, protein carbonyl content, serum nitric oxide, cholesterol/phospholipid ratio (C/P) of erythrocyte and osmotic fragility were significantly increased in the case subjects compared to control. All of these reflect an oxidant-antioxidant imbalance in this setting. Thus, this study provides a detailed profile of the oxidant-antioxidant levels of the Bangladeshi cervical cancer patients, which revealed that the compromised antioxidant system in cervical cancer patients is associated with damage to various biomolecules and ultimately impairs cellular functions. J. Bangladesh Acad. Sci. 46(1); 117-128: June 2022